Knowledge, attitudes and practices on healthy lifestyle related behaviours among trainees of youth training centres in Sri Lanka - Dilini Mataraarachchi; P. V. S. C. Vithana; Ayesha Lokubalasooriya; Chamanthi Jayasundera; Suranutha Anton; Chithrammalee de Silva (College of Community Physicians of Sri Lanka, 2022)
Introduction: The adolescent and youth health module has been introduced to the youth training centres in 2017. Objectives: To assess the knowledge, attitudes and practices on healthy lifestyle-related behaviours including healthy eating practices, physical activity and substance misuse among youth trainees attached to youth training centres in Sri Lanka Methods: A descriptive cross-sectional study was carried out among a sample of 425 youth trainees aged 15-29 years from six youth training centres selected using simple random sampling technique, using a pre-tested self-administered questionnaire. Scoring system was developed for measuring knowledge, attitude and practices on healthy behaviour and percentage scores were presented with median and inter quartile range (IQR). Associated factors for accepted levels were identified using Chi-squared Test or Fisher's Exact Test. Results: All 425 participants responded. Majority (n=365; 85.9%) were Sinhalese, while 355 (83.6%) were Buddhists. Mean age was 18.6 years (SD=1.82). Most (n=344; 80.9%) were living in their own homes. Median percentage scores for knowledge, attitudes and practices on healthy lifestyle-related behaviours were 65.2 (IQR: 52.2, 69.6), 33.3 (25.0, 50.0) and 58.5 (48.1, 66.0), respectively. A majority, 80.7% (n=243) had an acceptable level of knowledge and 72.7% (n=309) an acceptable level of practice. Only 16.0% (n=68) had accepted level of attitudes. Youth trainee's ethnicity, religion, age, education level and participation in the youth health module training were significantly related to their knowledge in healthy lifestyle-related behaviour (p<0.05). However, none of these were significantly associated with trainee's attitudes on healthy behaviours although a significantly higher percentage of older youth were found to have healthy attitudes towards healthy behaviour. Conclusions & Recommendations: It is recommended to revise the training module, focusing more on attitudinal change with regards to the healthy lifestyle related behaviours. Delivery of the youth health module in both Sinhala and Tamil languages needs to be looked into.